1992
DOI: 10.1007/bf01962701
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of valproate to hepatotoxic intermediates

Abstract: A number of lines of evidence indicate that metabolites of valproate rather than the parent drug, mediate the microvesicular steatosis which characterizes valproate-associated liver injury. In this article, two mechanisms are discussed whereby valproate may cause hepatic steatosis through interference with the process of fatty acid beta-oxidation. In the first, valproate itself enters the mitochondrion where it completes for the enzymes and/or co-factors involved in the beta-oxidation of endogenous substrates,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 29 publications
1
21
0
Order By: Relevance
“…Glucuronidation and β-oxidation are quantitatively the most important routes of biotransformation, generating a complex pattern of intermediates (Baillie 1992) which could potentially interfere with mitochondrial metabolism at different levels. In the past, several papers have described inhibitory effects of VPA and its metabolites on mitochondrial oxidative phosphorylation, both in vitro (Haas et al 1981;Becker and Harris 1983;Ponchaut et al 1992) and in vivo (Rumbach et al 1983).…”
Section: Short Communicationmentioning
confidence: 99%
“…Glucuronidation and β-oxidation are quantitatively the most important routes of biotransformation, generating a complex pattern of intermediates (Baillie 1992) which could potentially interfere with mitochondrial metabolism at different levels. In the past, several papers have described inhibitory effects of VPA and its metabolites on mitochondrial oxidative phosphorylation, both in vitro (Haas et al 1981;Becker and Harris 1983;Ponchaut et al 1992) and in vivo (Rumbach et al 1983).…”
Section: Short Communicationmentioning
confidence: 99%
“…The results of these studies showed that metabolism, which does not occur in HLMs with NADPH, is also an important factor. Examples involve the acyl glucuronides of zomepirac (Wang et al, 2001) and valproic acid (Kumar et al, 2000) and the ␤-oxidation of valproic acid (Baillie, 1992). In this study, zomepirac and valproic acid were not assessed as having a positive risk of forming RMs in either the […”
Section: Discussionmentioning
confidence: 89%
“…VPA is well absorped orally and metabolized in the body by a combination of mitochondrial, microsomal and cytosolic enzymes to produce at least 20 known metabolites [104]. Due to large interindividual differences in metabolic rate, there is a poor correlation between dose and serum concentration of VPA, especially in patients who are comedicated with enzyme-inducing AEDs [105,106].…”
Section: Valproic Acid (Vpa)mentioning
confidence: 99%
“…Ideally samples for VPA measurements should be drawn before the morning dose [21,109]. For quantificative methodology for VPA, GC is considered as analytical method of choice for the simultaneous determination of VPA and its 5∼20 metabolites [110,111] and for metabolism studies or VPA hepatoxicity studies [104]. GC methods with either MS or FID were obviously widely used for the determination of unchanged VPA only or VPA and some unsaturated metabolites or VPA in the presence of other AEDs [112].…”
Section: Valproic Acid (Vpa)mentioning
confidence: 99%